2013
DOI: 10.5012/bkcs.2013.34.12.3597
|View full text |Cite
|
Sign up to set email alerts
|

Dual Substituent Effects on Anilinolysis of Bis(aryl) Chlorothiophosphates

Abstract: The reactions of bis (Y-aryl) chlorothiophosphates (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…6 The sign of ρ XY was negative with 2, while the sign of ρ XY was positive for both electrondonating and -withdrawing Y substituents despite biphasic concave upward free energy relationships. This indicated that the reaction mechanism was changed from a concerted (or a stepwise with a rate-limiting bond formation) with 2 to a stepwise with a rate-limiting bond cleavage with 1 due to additional substituent Y.…”
mentioning
confidence: 95%
“…6 The sign of ρ XY was negative with 2, while the sign of ρ XY was positive for both electrondonating and -withdrawing Y substituents despite biphasic concave upward free energy relationships. This indicated that the reaction mechanism was changed from a concerted (or a stepwise with a rate-limiting bond formation) with 2 to a stepwise with a rate-limiting bond cleavage with 1 due to additional substituent Y.…”
mentioning
confidence: 95%